Non-contact luminescence lifetime microthermometry using scintillation sensors - Mykhaylyk, V; Kraus, H; Wagner, A (Polish Academy of Sciences Institute of Physics, 2017)
The paper describes an original technique for non-contact in situ monitoring of the temperature developed for experiments in a vacuum environment at the tender X-ray beamline I23 of the Diamond Light Source. The sample temperature is established by determining the luminescence decay constant of a Bi4Ge3O12 (BGO) scintillation sensor. BGO is ideally suited for a temperature range of 30 K to 130 K, in which its decay constant shows a strong temperature dependence. The principle of the method, system design and application examples are discussed and the performance and potential of the technique is assessed.